Problems of training specialists in the field of digital transformation: The experience of Russia - E. V. Romanov (Образование и наука)
Introduction. The structural reorganisation of the Russian economy will require a revision of approaches to training specialists in the field of information technology in the context of the “war for talents” unfolded in the world. HR digital revolution (digital transformation) is one of the conditions for Russia’s breakthrough into the sixth technological order to ensure digital sovereignty in Russia.Aim. On the basis of identifying significant problems in the adaptability of the Russian higher education system to provide national economy with personnel, the present research aimed to formulate approaches to the strategy aimed at determining the number of university admission quotas in training programmes related to digital transformation.The literature highlights two serious problems regarding the policy of distribution of admission quotas for higher education programmes: 1) the allocated admission quotas for the most part do not correspond to the structure of the regional economy; 2) violation of the norm of the number of students per 10 thousand of the population aged 17 to 30 years, as a result, in some regions, the number of school graduates significantly exceeds the number of budget places in universities. The hypothesis of the study consists in the assumption that the policy of distribution of admission quotas for training in higher education programmes is flexible, providing for an increase in enrolment for training in areas related to information and communication technologies with an increase in “demand” for training in these areas.Methodology and research methods. The work was carried out on the basis of a systematic approach. Theoretical research methods (methods-operations) were used: analysis (literature on the research problem, normative documents), comparison and generalisation, induction, synthesis. The main theoretical method-action was the inductive-deductive method. At the first stage of the study, the analysis of the number of students enrolled for full-time study (computer science and computer engineering) at the expense of federal budget allocations (period 2016–2021) was carried out. As a result of data generalisation in certain areas of training and comparative analysis of the number of applicants with the allocated admission quotas, the discrepancy (gap) between compared values was established. At the second stage of the research, similar methods were used in areas related to computer and information sciences and information security to confirm the systemic nature of the identified phenomenon.Results and scientific novelty. Based on the analysis of the admissions (period 2016– 2021) to the specialities related to information technology (computer science and computer engineering, computer and information science, information security), the author has identified a gap between admission to the university and admission quotas. The essence of this gap is that in the analysed areas of training, the number of full-time students accepted for full-time education at the expense of federal budget allocations is significantly lower than the volume of allocated admission quotas. Thus, according to the enlarged groups of specialities (EGS) “Computer Science and Computer Engineering”, the number of accepted undergraduate and graduate programmes was less than the allocated admission quotas for 37519 university places (17075 + 20444); the gap in the speciality “Computer and Information Sciences” (bachelor degree programme + master degree programme) was 3584 (1722 + 1862); “Information Security” (bachelor degree programme + specialist degree programme) – 4082 (1393 + 2689). The possible causes of the gap are analysed and proposals are formulated to improve the institutional provision of training for digital transformation.Practical significance. The research results can be used to adjust the strategy for the development of scientific and educational sphere.